Analysis of Code Mixing in Student Conversations of Islamic Religious Education Study Program at IAID Martapura - fizi (Fakultas Tarbiyah IAI Darussalam, 2025)
Nowadays, people usually speak more than one language, especially college students. They often mix English vocabulary in their daily conversations. This phenomenon attracted the attention of researchers to investigate code mixing in daily conversations among students of Islamic Religious Education Study Program at IAID Martapura and the reasons for using code mixing. This study uses a descriptive qualitative research design with 15 Islamic Religious Education students as research subjects. The subjects were selected using the purposive sampling technique. Data were obtained through observation and interviews. The observation is intended to obtain data on the form of use of mixed codes. The data was then analyzed based on the mixed form of code proposed by Suwito (1983). Meanwhile, interviews are used to obtain data on the reasons for using code mixing. To analyze the data, researchers used an interactive model from Miles, Huberman and Saldana (2014). The results showed that code mixing at the dominant word level occurred which reached 14 words (66.7%). The main reason for using code mixing is because of the student environment.